EV‐Chips Sensors: Rapid and Electronic Identification and Quantification of Age‐Specific Circulating Exosomes via Biologically Activated Graphene Transistors (Adv. Biology 7/2021). Issue 7 (7th July 2021) - Hajian, Reza; DeCastro, Jonalyn; Parkinson, Jonathan; Kane, Alex; Camelo, Andres Felipe Romero; Chou, Peichi Peggy; Yang, Jielin; Wong, Nathan; Hernandez, Ecson Daniel Obando; Goldsmith, Brett; Conboy, Irina; Aran, Kiana
Abstract : In article number 2000594, Kiana Aran and co‐coworkers show exosomes binding to a graphene field‐effect transistor (gFET), termed EV‐chip. The EV‐chip enables label‐free, rapid, point‐of‐care identification and quantification of blood‐derived exosomes containing biomarkers associated with cancer and other age‐related diseases. The sensor is ideal for use in a physician's office or a simple biological laboratory. Image credits: Ella Maru Studio.